Descrição e análise do comportamento de crianças na resolução de problemas lógicos - Bitencourt, Lígia Cristina (2009)
The process of problem solving behavior is logical, as opposed to a set of conditions, manipulate the individual variables (preliminary behavior) that changes the situation or the person generating discriminative stimuli that control later responses, and analyze data resulting from such manipulations allowing the issue of response-solution. The primary objective of this research was to describe and analyze the behavior of children and identify factors that control the situation or did not respond. To collect data we used two sets of rules available commercially: Senha and Boole. Both games were applied to six male children, aged 8 years and 10 months and 10 years. The design was composed of two experimental conditions: the basic procedure and additional procedures. The procedure-based contained three levels of difficulty (level 1, level 2 and level 3), which were overcome by the issue of response-solution. The additional procedures were added when the participant failed to give the answer with the solution within the criteria proposed in the basic procedure. The responses of the participants determined the manipulations performed. The analysis of the behavior of children showed some manipulation of stimuli to encourage the issue of response-solution in each of the games. However, a manipulation that was central to both was the deduction, which was identified through verbal and nonverbal responses of participants. The difficulty encountered in making a deduction appeared in conditional sentences. Only one participant acted under control of conditional rules to solve the problem correctly. Password for the game, specifically, an aspect that was seen as relevant was linked to the fact that the participant can not or do inductions. The manipulation of variables being the center of this process, the deductions and inductions made by the participants, specifically the derivation and / or formulation of rules, may be regarded as directory prerequisite to problem-solving software. The lack or a failure in the implementation of such manipulation impossible to issue the response-solution for the individual, which could be demonstrated in the results presented. Whereas formal education seeks to train individuals able to solve problems, the results of research become important in that they point to intervening variables that allow the installation of a repertoire suitable for solving problems of logic